Mesenchymal stem cells and their secretome modulate stress and enhance lipogenesis in bovine mammary epithelial cells - Roni Tadmor-Levi; Lior Sharabi; Adi Koren; Sharon Schlesinger; Noam Tzirkel-Hancock; Nurit Argov-Argaman (Stem Cell Research & Therapy, 2025)
Abstract Background Increased production of the modern dairy cow can induce a stress response by the mammary epithelial cells (MEC) and compromise production traits. To alleviate this stress response, various strategies have been tested. Previous studies have shown an immunomodulatory effect of mesenchymal stem cells (MSC) and their secretome on different cell types and tissues; however, their effect in the context of lactation performance has not yet been studied. In this study, we aimed to assess the effects of MSC and their secretome on the stress response and lipogenesis in bovine MEC. Methods We measured gene expression, lipid droplet (LD) characteristics, and triglyceride content in bovine MEC subjected to stress. The effect of co-culturing with MSC or their secretome, used as conditioned media (CM) was evaluated in the same context. Results In MEC, lipopolysaccharide (LPS) triggered a progressive rise in pro-inflammatory cytokines, while H2O2 predominantly activated lipogenic pathways. More specifically, acetyl-CoA carboxylase (ACC) expression significantly increased in response to H2O2, whereas no change was observed in LPS-treated cells. Fatty acid synthase (FASN) expression decreased under LPS and remained unchanged under H2O2. Stearoyl-CoA desaturase (SCD1) expression was significantly elevated by LPS but remained stable under H2O2. Both stressors increased triglyceride content of MEC after 48 h and reduced intracellular LD size. When MEC were co-cultured with MSC, the response to LPS was attenuated, as indicated by lower expression of the pro-inflammatory genes, interleukin 6 (IL-6) and tumor necrosis factor α (TNFα). Using MSC secretome as CM for MEC led to reduced expression of TNFα and IL-6 under both basal conditions and in response to LPS. Interestingly, independent of external stress, MSC secretome significantly increased the expression of all lipogenic genes, including FASN, ACC and diacylglycerol acyl-transferase (DGAT). Conclusions These results demonstrate that the lipogenic capacity of MEC as well as their intracellular LD size and number, are integral to the stress response. MSC exerted an immunomodulatory effect on MEC and enhanced their lipogenic capacity. This effect is at least partly mediated by paracrine factors, and does not require physical contact between MEC and MSC. Further studies are warranted to identify the bioactive components, which could be used to enhance MEC bioactivity during lactation.